PENGARUH INTENSITAS MUSIM HUJAN TERHADAP KELIMPAHAN FITOPLANKTON DI WADUK BENING SARADAN - Klaudia Putri Nirmalasari; Marheny Lukitasari; Joko Widianto (JEMS: Jurnal Edukasi Matematika dan Sains, 2014)
This study aims to determine the effect of the intensity of the rainy season to the abundance of phytoplankton in the reservoir Bening Madison County. As well as exploit some results of research on the abundance of phytoplankton as a medium of learning materials were shaped poster on the types of phytoplankton. This study uses a quantitative approach to the exploration technique. There are six points each station with two sample replicates. The results showed that in Reservoir Bening Saradan found 16 species of phytoplankton that is Synedra acus, Synedra ulna, Navicula grevillei, Tetragonodium verum, Crucigenia rectangularis, Ulothrix cylindricum, Nitzchia paleaceae, Ceratium candelabrum, Goniochloris sculpta, Scenedesmus ocuminatus, Navicula sp, Nitzchia acicularis, Spirulina major, Ceratoneis acus, Pediastrum simplex, Pleurota eniumtrabecula. Phytoplankton abundance is the most ubiquitous class Bacillariophyceae. Phytoplankton abundance is influenced by monsoon intensity 40,9%. While 59,1% of other factors influenced the agricultural wastes that contain elements of N, P, K, which can improve nutrient. The highest phytoplankton abundance in December is 138,64 ind/l with 12 species of phytoplankton. The number of rainy days in the December low at 25/31 days allows a maximum of phytoplankton photosynthesis. Lowest phytoplankton abundance in February which is 65,14 ind/l. Phytoplankton abundance is directly proportional to the intensity of the rainy season. The number of higher intensity, phytoplankton abundance is also higher, and vice versa. Physical and chemical conditions Bening Reservoir categorized according to the results of research in the waters of the state are less fertile and less than optimal for the growth ofphytoplankton.